A study to analyze the performance level of the high spike and serve skills of professional players in the Iraqi Volleyball Premier League for the 2022-2023 season - almaliki, tabark; Khalaf , Naeema (Journal of Physical Education, 2024)
The importance of research in analyzing the level of offensive skill performance for the high smash and serve skills according to a computer-based analysis program on professional players in the Iraqi Premier League in volleyball. Through the researcher’s follow-up of the matches of the Iraqi Premier League in volleyball, they found that the clubs that contracted with professional players there is a disparity in the level The skill performance of these professionals, especially the level of performance of some offensive skills. The objectives of the research were to analyze the level of skill performance of professional players for the serving skill and to analyze the level of skill performance of professional players for the spike hit skill according to the location of the spike hit on the court (1, 2, 4). The researcher used the (data) program. volley) to analyze the effectiveness of the offensive skill performance of professional players, which extracts an analysis of the level of skill performance for the serving and spiking skills. The conclusions of the research were There is a weakness in the level of performance of the serve skill of both types of ace and fluter among professional club players, and the level of performance of the ace skill from position (2) is better than the level of performance of the skill of ace from position (4). There is a discrepancy in the performance level of the skill of ace from position (1). ) between one match and another based on the level of performance of the competing team. The recommendations were training on accuracy, concentration and speed in hitting the ball on the ace and fluter to increase effectiveness and introduce fun and suspense into training types of serves as well as increasing motivation.